Possible impact of the latest international standard of auditing 570 on the rate of going concern opinion issuance in Malaysia - Osman, Mohammad Noor Hisham; Abdul Latiff, Ahmed Razman; Mat Daud, Zaidi; Muhamad Sori, Zulkarnain; Turmin, Siti Zaidah (Faculty of Technology Management and Business, Universiti Tun Hussein Onn Malaysia, 2018)
The problem that Malaysian auditors do not issue going concern opinion (GC opinion) to seriously financially distressed companies is still a pressing issue. The latest International Standards on Auditing 570 Going Concern (ISA 570) has been released and made effective in Malaysia starting from 15th December 2016. It is reasonable to expect that the new ISA 570 (2016) could at least reduce the incidence of Malaysian auditors do not want to issue GC opinion to financially distress companies. Overall, we are in the opinion that there is no strong ground to expect the new ISA (2016) can reduce the problem of Malaysian auditor do not issue GC opinion to a very large percentage of seriously financially distress companies. This is because there is no new stricter measure has been introduced in the latest ISA 570 (2016). However, Malaysian policy makers and standard setters still have at least four measures if they want to improve the rate and practice of GC opinion issuance in this country. Researchers on the other hand should examine the effectiveness of the new ISA 570 (2016), at least.